Optimizing treatment for diabetic macular edema during cataract surgery - Chan, Leo Ka Yu; Lin, Sui Sum; Chan, Fiona; Ng, Danny Siu-Chun (Frontiers in Endocrinology, 2023)
Diabetic macular edema (DME) causes visual impairment in diabetic retinopathy (DR). Diabetes mellitus is a global epidemic and diabetic individuals are at risk of developing DR. About 1 in 10 diabetic patients suffers from DME, which is the commonest cause of vision-threatening DR at primary care screening. Furthermore, diabetes predisposes to higher frequency and younger onset of cataract, which further threatens vision in DME patients. Although cataract extraction is an effective cure, vision may still deteriorate following cataract surgery due to DME progression or recurrence, of which the risks are significantly higher than patients without concurrent or previous history of DME at the time of operation. Management of pre-existing DME with visually significant cataract is a clinical conundrum. Deferring cataract surgery until DME is adequately treated is not ideal because of prolonged visual impairment and maturation of cataract jeopardizing surgical safety and monitoring of DR. On the other hand, progression or recurrence of DME following prompt cataract surgery is a profound disappointment for patients and ophthalmic surgeons who had high expectations for post-operative visual improvement. Prescription of perioperative anti-inflammatory eye drops is effective in lowering the risk of new onset DME after cataract surgery. However, management of concurrent DME at the time of cataract surgery is much more challenging because DME is unlikely to resolve spontaneously even with the aid of anti-inflammatory non-steroidal or steroid eye drops. A number of clinical trials using intravitreal injection of corticosteroids and anti-vascular endothelial growth factor (anti-VEGF) as first-line therapy have demonstrated safety and efficacy to treat DME. These drugs have also been administered peri-operatively for the prevention of DME worsening in patients undergoing cataract surgery. This article reviews the scientific evidence to guide ophthalmologists on the efficacy and safety of various therapies for managing patients with DME who are particularly vulnerable to cataract surgery induced inflammation, which disintegrates the blood-retinal barrier and egression of fluid in macular oedema.